Rapidly Increasing Severe Acute Respiratory Syndrome Coronavirus 2 Seroprevalence and Limited Clinical Disease in 3 Malian Communities: A Prospective Cohort Study - Issaka Sagara; John Woodford; Mamady Koné; Mahamadoun H. Assadou; Abdoulaye Katilé; Oumar Attaher; Amatigué Zéguimé; M’Bouye Doucoure; Emily Higbee; Jacquelyn Lane; Rathy Mohan; Justin Doritchamou; et al. (2021)
The extent of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure and transmission in Mali and the surrounding region is not well understood. We aimed to estimate the cumulative incidence of SARS-CoV-2 in 3 communities and understand factors associated with infection.